Adaptive Torque and Position Control for a Legged Robot Based on a Series Elastic Actuator. (12th February 2016) - Zhu, Qiuguo; Mao, Yichao; Xiong, Rong; Wu, Jun
Inspired by biological systems, we seek to achieve natural dynamics and versatile locomotion for hopping or running robots by installing a series elastic actuator (SEA) in the joints due to its compliant property, passive adaptability and energy storage. However, robots equipped with these actuators have drawbacks in terms of substantial delay and limited bandwidth in their position control, especially when a robot has to choose its foothold while it is running at a demanding speed. To solve these problems, compliance control and adaptive position/torque control are introduced to a hopping- legged robot in this paper. The compliant performance of the robot can be improved through the intrinsic property of an SEA with a torque control algorithm. Combining the kinetics model and stochastic model of a 2-DOF robot, an adaptive position control with Kalman Filtering (KF) is developed to provide rapid convergent state estimation of the load on the robotic end-effector by solving the inverse dynamics. Validating the robustness and effectiveness of the proposed algorithm on our hopping-legged robot Tigger, the experimental results show very good position-tracking and disturbance-rejection, as well as flexible interactions while operating in a complex environment.